Environmental Licensing for Hydroelectric Projects in Brazil : A Contribution to the Debate - World Bank (Washington, DC, 2012)
This study points out that hydroelectric plants will continue to play a prominent role in the Brazilian electric matrix. A significant portion of the potential hydroelectric plants of the country is located in the Amazon, environmentally sensitive region. The licensing of hydroelectric projects in Brazil is considered a major obstacle for the expanding the capacity of generating electricity. The non-expansion, in turn, represents a serious threat to economic growth. This study, designed as a contribution to the debate in progress about the subject, examines the legal and institutional milestones of the environmental licensing of hydroelectric ventures, including studies of selected cases, an assessment of transaction costs of the processes and a comparison with international practices. Two conclusions emerge from this study. The first is that the costs of dealing with environmental issues and social development of enterprises hydroelectric in Brazil represent 12 percent of the total cost of the work. And the second is that costs of taxes, in general, the contractual and regulatory uncertainty, excluding the licensing environmental, represent about 7.5 percent of the total cost. In other words, the conclusion is clear: the environmental and social costs can be easily integrated. This study does not suggest radical changes to the system of environmental licensing. Any reform of the Brazilian environmental licensing can not be dealt with based on a single, simple solution. Rather, the system is complex and multifaceted, with a long legal and institutional history. A process of broad national discussion on the energy issue and its implications for environmental goods of the country is essential and is already in progress.